THE CONCEPT OF WRITING IN THE QUR'AN: ANALYSIS OF THE TERMS KATABA, KHAT, AND SATARA - Armita, Pipin; Saad, Mohd Faizulamri Mohd (Universitas Muhammadiyah Surakarta, 2023)
In the Qur'an, there are several terms that lead to the notion of writing, such as Kataba, Khat, and Satara. Etymologically, these three terms have different aims and purposes. As for the method used in this study, because this type of research is qualitative research, the data used is sourced from the literature, namely all data and materials used are data or library materials that are appropriate to the issues raised. Library materials used as research objects are books, journals, magazines, or other writings related to 'writing' in the Qur'an. In this study, there are two data sources used by researchers, namely primary data sources and secondary data sources. Thus, the results of this study are that there are three concepts of writing in the Qur'an as a way of life for Muslims, namely Kataba, Khat, and Satara. From the results of observations, it is known that these three concepts are mentioned directly in the Qur'an, and that is what distinguishes them from other writing concepts, and these three writing concepts can be used as a solution to increase the literacy interest of the Indonesian people.